Alpha-helical destabilization of the Bcl-2-BH4-domain peptide abolishes its ability to inhibit the IP3 receptor. - Giovanni Monaco; Elke Decrock; Koen Nuyts; Larry E Wagner; Tomas Luyten; Sergei V Strelkov; Ludwig Missiaen; Wim M De Borggraeve; Luc Leybaert; David I Yule; Humbert De Smedt; Jan B Parys; et al. (PLoS ONE)
The anti-apoptotic Bcl-2 protein is the founding member and namesake of the Bcl-2-protein family. It has recently been demonstrated that Bcl-2, apart from its anti-apoptotic role at mitochondrial membranes, can also directly interact with the inositol 1,4,5-trisphosphate receptor (IP3R), the primary Ca(2+)-release channel in the endoplasmic reticulum (ER). Bcl-2 can thereby reduce pro-apoptotic IP3R-mediated Ca(2+) release from the ER. Moreover, the Bcl-2 homology domain 4 (Bcl-2-BH4) has been identified as essential and sufficient for this IP3R-mediated anti-apoptotic activity. In the present study, we investigated whether the reported inhibitory effect of a Bcl-2-BH4 peptide on the IP 3R1 was related to the distinctive α-helical conformation of the BH4 domain peptide. We therefore designed a peptide with two glycine "hinges" replacing residues I14 and V15, of the wild-type Bcl-2-BH4 domain (Bcl-2-BH4-IV/GG). By comparing the structural and functional properties of the Bcl-2-BH4-IV/GG peptide with its native counterpart, we found that the variant contained reduced α-helicity, neither bound nor inhibited the IP 3R1 channel, and in turn lost its anti-apoptotic effect. Similar results were obtained with other substitutions in Bcl-2-BH4 that destabilized the α-helix with concomitant loss of IP3R inhibition. These results provide new insights for the further development of Bcl-2-BH4-derived peptides as specific inhibitors of the IP3R with significant pharmacological implications.